2015
DOI: 10.3389/fneur.2015.00238
|View full text |Cite
|
Sign up to set email alerts
|

Recovery Potential After Acute Stroke

Abstract: In acute stroke, the major factor for recovery is the early use of thrombolysis aimed at arterial recanalization and reperfusion of ischemic brain tissue. Subsequently, neurorehabilitative training critically improves clinical recovery due to augmention of postlesional plasticity. Neuroimaging and electrophysiology studies have revealed that the location and volume of the stroke lesion, the affection of nerve fiber tracts, as well as functional and structural changes in the perilesional tissue and in large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 212 publications
(217 reference statements)
3
30
0
3
Order By: Relevance
“…However, therapeutically, this approach runs counter to practice in sensorimotor stroke, where it has been shown that early injury responses heighten neuroplastic potential (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…However, therapeutically, this approach runs counter to practice in sensorimotor stroke, where it has been shown that early injury responses heighten neuroplastic potential (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the intervention in all studies was well monitored and supported the aim of the studies. As all studies included chronic stroke survivors to avoid contamination with other recovery potentials following stroke [34]. Blinded assessments were reported in most studies to reduce or eliminate bias even though in most studies it was a single-blinded design [35].…”
Section: Quality Reviewmentioning
confidence: 99%
“…This can be seen in the cross tabulation as follows: Therefore it can be concluded that the left side area of the brain is more dominant than on the right side [7]. the limb side space, and Gerstman syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…The location and volume or extent of cerebral infarction determine neurologic deficits in stroke patients especially in sensorimotor, cognitive and emotional functions. The infarction in the cerebellum can affect some brain systems that can lead to complex neurological syndromes, such as apraxia, inability to notice the limb side space, and Gerstman syndrome [3].…”
Section: Introductionmentioning
confidence: 99%